Efficiency of enterosorption in gastrointestinal allergy in young children - T. G. Malanicheva; N. V. Ziatdinova; Z. R. Sharkhymullina; V. A. Olshansky (Лечащий Врач)
Food allergies are among the most common allergic diseases in children. Allergic damage to the gastrointestinal tract in young children is associated with the influence of genetic factors and sensitization of the body to food allergens, and primarily to cow's milk proteins. Gastrointestinal allergy ranks second among the pathologies associated with food allergies. With gastrointestinal allergies caused by food allergens, allergic inflammation develops in the gastrointestinal tract. Damage to the mucous membrane is accompanied by the penetration of bacterial endotoxin (lipopolysaccharide) from the intestinal lumen into the bloodstream, which leads to disruption of microcirculation processes in the mucous membrane and the development of its ischemia. The processes of its regeneration are disturbed and the processes of damage are intensified. For this reason, children with gastrointestinal symptoms of allergy are shown to prescribe drugs that have a sorption and cytoprotective effect. A significant improvement in the morphofunctional state of the intestinal mucosa is noted as a result of the use of the enterosorbent. This study showed the effectiveness of organosilicon enterosorbent in children with gastrointestinal allergy aged 2 months to 1 year. An open prospective randomized clinical trial was conducted at the Children's Republican Clinical Hospital in Kazan. Informed consent was obtained from the parents of all children for inclusion in the study. 57 children with gastrointestinal forms of allergy were under observation. Boys made up 52.6%, girls – 47.4%. The appearance of symptoms of gastrointestinal allergy in children is associated with the transfer to artificial feeding with adapted mixtures based on cow's milk. The inclusion of organosilicon enterosorbent in the complex antiallergic therapy at an age dosage leads to a positive clinical effect in 90% of cases with a 1.5-fold reduction in the exacerbation period against the background of a decrease in the level of total IgE and specific IgE to cow's milk proteins and casein. Silicone enterosorbent can be recommended for infants with gastrointestinal manifestations of food allergy to cow's milk proteins in combination with diet therapy and antihistamines.